Anthropometry-based Body Fat Percentage Predicts High hs-CRP in Chronic Kidney Disease Patients - Mochammad Thaha; Maulana Antiyan Empitu; Ika Nindya Kadariswantiningsih; Cahyo Wibisono Nugroho; Nurina Hasanatuludhhiyah; Haerani Rasyid; Zaky El Hakim; Maulana Muhtadin Suryansyah; Rieza Rizqi Alda; Mohammad Yusuf Alsagaff; Mochammad Amin; Djoko Santoso; Yusuke Suzuki (The Indonesian Biomedical Journal, 2018)
BACKGROUND: Obesity is an important cardiovascular risk factor and associated with low grade inflammation in chronic kidney disease (CKD) patients. This study aims to assess the association between body fat with serum high sensitivity C-reactive protein (hs-CRP) level in CKD patients.METHODS: A cross-sectional study was performed in 71 CKD patients. Anthropometric measurements included body weight, height, body mass index (BMI), body fat percentage (BFP), skinfold thickness (SKF) of triceps and biceps were performed by trained physician. BFP was calculated using Kwok’s Formula and hs-CRP was measured by Particle enhanced Turbidimetry.RESULTS: The averaged BMI of our subjects was 25.8±4.4. There was no significant difference in BMI between pre-dialysis and hemodialysis CKD patients. Positive correlation was found between BFP and hs-CRP (r=0.266; p<0.05), while there was no significant correlation between BMI and hs-CRP.CONCLUSION: Body fat percentage was associated with hs-CRP. Hence, it will be more beneficial to assess nutritional status in CKD using BFP rather than BMI alone since it was demonstrated to correlate with hs-CRP in our studyKEYWORDS: CKD, obesity, inflammation, body fat, hs-CRP